Aplikasi Berbasis HP untuk Mendukung Sistem Informasi Kebencanaan - Slamet Aji Pamungkas; Aditiyawan Aditiyawan (Bina Nusantara University, 2010)
The use of hand phone (HP) as a means of communication is prevalent in all societies in Indonesia. HP-based applications, of course, be a very useful innovation and facilitate all parties to operate the application. Java (J2ME) -based Technology is able to create applications that can be installed almost in all types of HP that exist in Indonesia. How it works using the HP-based applications for Disaster Information System are: the application based on Java (J2ME) installed on HP, then the application will be connected to web service on the Disaster Information System Server. In addition to uploading images, photos or video an event (events), the application is also equipped with the detection of spatial coordinates of the scene.